The prevalence of the metabolic syndrome in men presenting with erectile dysfunction at a South African tertiary care centre - Wood, Bradley Ryan (My University, 2010)
The metabolic syndrome has recently become one of the major public health challenges and results from the increasing prevalence of obesity. Erectile dysfunction (ED) affects up to half of men over the age of forty. Men with co-morbid disease and risk factors including cardiovascular disease, hypertension, dyslipidaemia and depression all report a higher prevalence of ED. The current study investigated the prevalence of the metabolic syndrome in one hundred men with (ED) presenting to the Male Sexual Dysfunction Clinic at the Johannesburg Hospital. Participants underwent a thorough history taking and examination session which included the International Index of Erectile Function Score. Several fasting biochemistry and hormonal tests were performed. Participants were divided by race into three groups. Data was recorded in EXCEL and reported as mean±std or as a number (frequency). Where applicable, correlation between variables was determined. The prevalence of the metabolic syndrome was 39%, with the highest prevalence (54%) in the group comprising Asian, Coloured and Chinese participants. Eighty percent of participants had moderate-severe (ED), with a mean duration of 3,8 years. Glucose and HbA1c were strong predictors of ED duration. Severity of ED was not influenced by the presence of the metabolic syndrome. Men presenting with ED may represent an ideal patient group to screen for the metabolic syndrome, and therefore for cardiovascular disease, especially for those men within the asymptomatic period.
MMed (Urology), Faculty of Health Sciences, University of the Witwatersrand
Keywords: metabolic syndrome; erectile dysfunction